Hubungan antara loneliness dengan durasi penggunaan media sosial pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2021 - Rarung, Citra; Pali, Cicilia; Opod, Hendri (Jurnal Kedokteran Komunitas dan Tropik, 2024)
Background: The occurrence of loneliness is very prominent for adolescents as their desire to feel socially accepted and belonged is very strong during the process of growth and development. Loneliness itself is a prominent aspect of the life course principle of interconnectedness. This relates to how adolescents perceive the quality of their relationships, i.e. how their lives are connected to others and how this affects mental and physical well-being. Research results on mood elevation claim that people with negative emotional states tend to seek solace online through social media. Over a span of 6 years, the number of teens with smartphone use grew from 4 in 10 teens to 9 in 10 teens.  In the same time span, the percentage of teens using social media doubled from 34% to 70%. Methods: This study is an observational analytic with a cross-sectional approach, applying the total sampling method. The sample was drawn through the distribution of questionnaires using Google form links during September-October 2023. Analysis of the correlation used the Spearman Rank test. Results: This study involved 276 student participations. There is a correlation between loneliness and the duration of social media use among 2021 students of the Faculty of Medicine, Sam Ratulangi University. The results show that the relationship between the two variables has a sufficient level of strength, a coefficient value of 0.354 and a positive correlation direction (p <0.001). Conclusion: The level of loneliness has a positive relationship with the duration of social media use in students of the Faculty of Medicine Sam Ratulangi University, class of 2021. Keywords: loneliness, duration of social media use, medical students